Analisis Gaya Bahasa dalam Pidato : Pasambahan Manyerak Bareh Kunyik - Pernando, Diki Dwi Putra; Ngusman, Ngusman (TSAQOFAH, 2024)
This research aims to analyze the language style in the pasambahan manyerak bareh kunyik in the city of Padang Panjang. This research explores the language styles in Pasambahan Manyerak Bareh Kunyik, a traditional Minangkabau art, with the aim of exploring the depth of the language styles and speech embedded in this performance. This research carries a stylistic approach with the aim of looking at the techniques and forms of a person's language style in presenting ideas in accordance with the ideas and norms used as well as the personal characteristics of the user. The term language style is not referred to the entire form of language use as discourse, but rather to words and units of speech that are considered to contain beauty. Therefore, the research carried out focuses more on units of expression in isolation, not on textual relationships. The method used in this research is the Listening Method to obtain data by listening to language use. The term listening here is not only related to the use of spoken language, but also the use of written language. Furthermore, the technique used here is the tapping technique which is referred to as the basic technique in the listening method because essentially listening is realized by tapping. In this article, researchers attempt to obtain data by tapping into the language use of a person or several people who are informants. In subsequent practice, this tapping technique was followed by a further technique in the form of free listening techniques without getting involved in the conversation, meaning that the researcher only acted as an observer of the informant's use of language and was not involved in the speech event whose language was being studied.